Study of Some Fungal Diseases of Tomato in Kathmandu Valley - Jha, Sanjay Kumar; Lamichhane, Sita (AMC Journal (Dhangadhi), 2023)
Tomato plants were observed and collected the infected part from Jitpurphedi of Kathmandu, Nepal. These infected parts were kept in pathology lab for fungal isolation. The isolated fungus from the infected tomato plants were as Septoria lycopersici, Cladosporium oxysporum were responsible for leaf spot, Phytophthora infestans and Rhizoctonia solani were responsible for Leaf blight, Cladosporium cladosporioides was responsible for fruit rot, Leveilullataurica was responsible for powdery mildew and Plasmoparaviticola was responsible for downey mildew disease. In the survey period, the highest incidence was found at leaf blight (30.08%) and lowest at stem rot (4.64%). In the case of severity, the maximum severity was found at Downey mildew (77%) and minimum was recorded at fruit rot (5.25%) on five different plastic houses.